2016
DOI: 10.1016/j.jcmgh.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Positively Regulates the Expression of pH-Sensing G-Protein–Coupled Receptor OGR1 (GPR68)

Abstract: Background & AimsA novel family of proton-sensing G-protein–coupled receptors, including ovarian cancer G-protein–coupled receptor 1 (OGR1) (GPR68) has been identified to play a role in pH homeostasis. Hypoxia is known to change tissue pH as a result of anaerobic glucose metabolism through the stabilization of hypoxia-inducible factor-1α. We investigated how hypoxia regulates the expression of OGR1 in the intestinal mucosa and associated cells.MethodsOGR1 expression in murine tumors, human colonic tissue, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 58 publications
3
29
0
Order By: Relevance
“…5). Our results provide confirmatory evidence of a crucial role for OGR1-mediated IRE1α/JNK activation in the induction of ER stress under low pH conditions, which might underlie the reported impact of OGR1 in the development of IBD 18,19 . In our previous studies, we observed significant and pH-dependent OGR1-mediated signalling, including IP3/Ca 2+ /ERK signalling and enhanced SRF transcription under acidic pH conditions (pH = 6.8) 17 .…”
Section: Discussionsupporting
confidence: 81%
“…5). Our results provide confirmatory evidence of a crucial role for OGR1-mediated IRE1α/JNK activation in the induction of ER stress under low pH conditions, which might underlie the reported impact of OGR1 in the development of IBD 18,19 . In our previous studies, we observed significant and pH-dependent OGR1-mediated signalling, including IP3/Ca 2+ /ERK signalling and enhanced SRF transcription under acidic pH conditions (pH = 6.8) 17 .…”
Section: Discussionsupporting
confidence: 81%
“…In MM6 cells, hypoxia-enhanced TNFα-induced GPR68 expression was also blocked by inhibition of NF-kB. Chromatin immunoprecipitation analysis revealed that in hypoxia, HIF-1α, but not NF-kB, binds to the GPR68 promoter [36].…”
Section: G Protein-coupled Receptor 68 (Gpr68/ogr1)mentioning
confidence: 99%
“…This places OGR1 in an exceptional position as it is synergistically activated by both and hence sensitive to even small changes. OGR1 can activate gene transcription pathways [39][40][41], is widely expressed in the human body [42], and overexpressed under pathological conditions [43,44]. Moreover, extracellular acidosis (at least in part via OGR1 itself) can promote cell stiffening by stimulating stress fibre formation [45], and OGR1 contributes to changes in extracellular matrix stiffness [46].…”
Section: Discussionmentioning
confidence: 99%